My Needs Network: How a Community-Based Participatory Research Process Morphed Into a Sustainable Community-Driven Networking Platform - Mark Fafard; Katryne Lukens-Bull; Meredith Pinard; Maria Bautista (Journal of Participatory Research Methods)
Children with complex medical conditions (CCMCs) require extensive care resulting in high levels of hospital and emergency room utilization, and a broad need for healthcare services, resources, and technology. Using a combined Grounded Theory and Community-Based Participatory Research (CBPR) approach, we aimed to discover the resource-related needs of CCMC families, identify ways to reduce hospital utilization, and increase their access to clinical and non-clinical resources.